1993
DOI: 10.1002/j.1460-2075.1993.tb05859.x
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of the poly(ADP-ribose) polymerase DNA-binding domain blocks alkylation-induced DNA repair synthesis in mammalian cells.

Abstract: The zinc‐finger DNA‐binding domain (DBD) of poly (ADP‐ribose) polymerase (PARP, EC 2.4.2.30) specifically recognizes DNA strand breaks induced by various DNA‐damaging agents in eukaryotes. This, in turn, triggers the synthesis of polymers of ADP‐ribose linked to nuclear proteins during DNA repair. The 46 kDa DBD of human PARP, and several derivatives thereof mutated in its first or second zinc‐finger, were overproduced in Escherichia coli, in CV‐1 monkey cells or in human fibroblasts to study their DNA‐binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
153
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(164 citation statements)
references
References 41 publications
10
153
0
1
Order By: Relevance
“…In these so-called COM3 cells, we could show that expression of dominant negative PARP sensitizes cells against g-irradiation and the alkylating agent MNNG, while there was neither an in¯uence detectable on DNA replication nor on cellular proliferation in the absence of genotoxic stress (KuÈ pper et al, 1995). This sensitization is associated with a block in DNA base excision repair (Molinete et al, 1993) and increased gene ampli®cation and sister chromatid exchanges (KuÈ pper et al, 1995Schreiber et al, 1995). We were then interested to see whether PARP DBD overexpression a ects tumor formation in nude mice.…”
Section: Generation Of Hela Cell Transfectants With Constitutive Overmentioning
confidence: 95%
“…In these so-called COM3 cells, we could show that expression of dominant negative PARP sensitizes cells against g-irradiation and the alkylating agent MNNG, while there was neither an in¯uence detectable on DNA replication nor on cellular proliferation in the absence of genotoxic stress (KuÈ pper et al, 1995). This sensitization is associated with a block in DNA base excision repair (Molinete et al, 1993) and increased gene ampli®cation and sister chromatid exchanges (KuÈ pper et al, 1995Schreiber et al, 1995). We were then interested to see whether PARP DBD overexpression a ects tumor formation in nude mice.…”
Section: Generation Of Hela Cell Transfectants With Constitutive Overmentioning
confidence: 95%
“…through overexpression of the DBD. also sensitizes cells to y-irradiation and alkylating acgents (Molinete et al 1993: Kupper et al 1995. an observation that is consistent with the effects of the benzamides being primarily caused by PARP inhibition.…”
mentioning
confidence: 99%
“…Horsman et al (1993 showed that there is no significant difference between the radiosensitising effect of NAM at doses of 100 mg kg-' and 1000 mg kg-1 in a C3H mammary carcinoma, even though the difference in plasma and tumour concentrations of NAM was 5-to 10-fold. These data have suggested an alternative explanation for the radiosensitising properties of NAM; namely that NAM at tumour concentrations of 100 juM or higher inhibits the PARP enzyme (IC50= 30 -100 gIM) (Molinete et al, 1993), which has been shown to be involved in DNA repair (Satho and Lindahl, 1994). The induced DNA damage at NAM doses of 100 and 1000 mg kg-' could be a result of PARP inhibition because of high tumour tissue levels of NAM (Figure 2), which in turn resulted in elevated NAD levels ( Figure 3) and accumulation of DNA damage (Figure 1).…”
Section: Nad Pools In Tumour Tissuementioning
confidence: 99%
“…The PARP enzyme is a DNAbinding enzyme with two zinc fingers in the DNA-binding domain (De Murcia et al, 1989;Molinete et al, 1993). The enzyme activity has been associated with DNA repair, apoptosis, cell proliferation, cell differentiation and genome surveillance (Althaus and Richter, 1987;Satoh et al, 1994;Kaufman et al, 1993;Dai et al, 1987).…”
mentioning
confidence: 99%